Design And Investigation of Sliding Mode Control Based DC-link Converter of Hybrid Microgrid System - P, Sai Sampath Kumar; P, Suresh; D.Lenine (International Journal of Integrated Engineering, 2024)
Hybrid Renewable Energy Systems (HRES) acts as optimal choice for the design of the electrical grid benefiting in social, economic and environmentally. This study interconnects wind, solar and Battery energy to transmit power to the load or grid thereby reducing the dependency on the conventional energy sources. Amidst the available non-conventional energy sources, this paper employs wind, solar and battery as the primary energy source for HRES. The suggested scheme involves wind driven permanent magnet synchronous generator, solar module, battery energy storage and necessary power converters along with suitable controllers. This investigation presents the Sliding Mode Controller (SLC) for maximum power extraction from wind and solar in order to maintain constant DC-link voltage. The generated power feeds the load through three-phase inverter. This paper compares the performance of the system using SMC and Perturb & Observe method (P&O) algorithm in Matlab/Simulink. The observed results prove the effectiveness of the SMC controller over P&O method with fast response during the change in operating condition.